2020
DOI: 10.1037/bul0000229
|View full text |Cite
|
Sign up to set email alerts
|

Human handedness: A meta-analysis.

Abstract: Across time and place, right hand preference has been the norm, but what is the precise prevalence of left-and right-handedness? Frequency of left-handedness has shaped and underpinned different fields of research, from cognitive neuroscience to human evolution, but reliable distributional estimates are still lacking. While hundreds of empirical studies have assessed handedness, a large-scale, comprehensive review of the prevalence of handedness and the factors which moderate it, is currently missing. Here, we… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
191
7
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 310 publications
(256 citation statements)
references
References 299 publications
13
191
7
5
Order By: Relevance
“…Our results show that, using a binary classification of writing hand as the criterion, around 8% of schoolaged children are left-handers. This estimate is lower than the most recently published value of 10.6% for the general left-handedness prevalence [11], but still higher than what was previously reported in Chinese. A 1980s survey found that less than 1% Chinese students were left-handed writers [24].…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…Our results show that, using a binary classification of writing hand as the criterion, around 8% of schoolaged children are left-handers. This estimate is lower than the most recently published value of 10.6% for the general left-handedness prevalence [11], but still higher than what was previously reported in Chinese. A 1980s survey found that less than 1% Chinese students were left-handed writers [24].…”
Section: Discussioncontrasting
confidence: 81%
“…Hand preference for writing can be easily collected as a tick-box questionnaire leading to large datasets. A recent meta-analysis estimated that the prevalence of left-hand preference in the general population is 10.6% based on data from over 2 million of people [11]. The study also confirmed the effect of some factors influencing hand preference including age, sex, and ethnicity reported in previous research.…”
Section: Introductionsupporting
confidence: 79%
See 1 more Smart Citation
“…In fact, it is well established that environmental pressures might force the use of the right hand for writing in left handers [13]. This phenomenon was mainly observed in past generations, and still applies to some cultures [1,14]. The EHI, similarly to other handedness questionnaires, leads to scores with a J-shaped distribution, indicating that the majority of people present an overall right-or left-hand preference with a few individuals in between.…”
Section: Introductionmentioning
confidence: 99%
“…Worldwide, the vast majority of people (roughly 90%) prefer using the right hand for most tasks in contrast to a minority of about 10% who prefer the left hand [1,2]. The 1 : 9 left to right ratio for hand preference is a feature specific to humans and is observed across populations.…”
Section: Introductionmentioning
confidence: 99%